Scarpetta - Cornwell, Patricia Daniels (Cornwell, Patricia Daniels. Scarpetta series., 2008)
Leaving behind her Charleston forensic pathology practice to accept an assignment in New York City, Kay Scarpetta learns the story of an injured psychiatric patient who claims he was attacked by a stalker who was killing someone else at the time.